Efficacy and safety of topical vs. oral calcium channel blockers for chronic anal fissures: a systematic review and meta-analysis - Li, Tianshuo; Ye, Pengfei; He, Xinli; Li, Chen; Xi, Lanlan; Xi, Zuowu (Frontiers in Pharmacology, 2025)
BackgroundCalcium channel blockers (CCBs) are first-line pharmacotherapy for chronic anal fissures (CAF), but the optimal administration route (oral vs. topical) remains unclear. This systematic review and meta-analysis compared efficacy and safety of oral vs. topical CCBs for CAF.MethodsPubMed and Embase were systematically searched from inception through February 2025 for relevant randomized controlled trials (RCTs). Two reviewers independently performed study selection, quality assessment, and data extraction. Random-effects models were used to pool effect sizes, with sensitivity analyses to assess robustness. The quality of evidence was assessed using the GRADE approach.ResultsFour RCTs (279 patients) were included. Topical CCBs significantly reduced unhealed fissure risk vs. oral CCBs (OR = 2.65, 95% CI = 1.50–4.69, moderate certainty evidence), with comparable recurrence rates (based on limited data from 3 studies). Initial side effect analysis showed no difference, but sensitivity analysis excluding a high-bias trial revealed fewer adverse events with topical CCBs (OR = 13.16, 95% CI = 5.05–34.3, moderate certainty evidence).ConclusionBased on limited evidence, topical CCBs may offer superior healing rates and safety profiles vs. oral formulations for CAF, with similar recurrence rates, though additional high-quality studies are needed to confirm these findings.